A comparison Some of Methods for Estimating Survival Function for Truncated Exponential Distribution - لازم جاسم حسن (Journal of Economics and Administrative Sciences, 2012)
Exponential distribution is one of most common distributions in studies and scientific researches with wide application in the fields of reliability, engineering and in analyzing survival function therefore the researcher has carried on extended studies in the characteristics of this distribution. In this research, estimation of survival function for truncated exponential distribution in the maximum likelihood methods and Bayes first and second method, least square method and Jackknife dependent in the first place on the maximum likelihood method, then on Bayes first method then comparing then using simulation, thus to accomplish this task, different size samples have been adopted by the searcher using (10, 20,30,50,100) results gained proved that second Bayes method domination upon all other method and for all samples